Mª A. DURÁN, Mª V. LÓPEZ-CORDÓN, R.Mª. CAPEL, O. GÓMEZ-FERRER, G.A. FRANCO, G. NIELFA, COLECTIVO 36, M.E. NICOLÁS y B. LÓPEZ: Mujer y Sociedad en España (1700 - 1975) - Pereira Castañares, Juan Carlos (Cuadernos de Historia Moderna y Contemporánea, 1983)
Sin resumen